1998
DOI: 10.1051/rnd:19980604
|View full text |Cite
|
Sign up to set email alerts
|

Embryo transfer and related technologies in sheep reproduction

Abstract: -This paper reviews the status of embryo transfer and the major technologies applied to preimplantation of embryos in sheep. Embryo production from superovulated ewes is hindered by an unpredictable response to hormonal treatment. Progress in this area should be expected by an appropriated control of follicular development with gonadotropin-releasing hormone (GnRH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…Some of these signs, such as impaired labor (weak propulsive stage) and little preparation of the mammary gland, have already been described following transfer of both IVP bovine [25] and NT [3,44] ovine and bovine embryos. Our previous studies revealed a failure of maternal contribution to the labor of recipients carrying IVP and NT pregnancies [45][46][47], and here we observe further physiological deficiencies during the initial phase of parturition, including a lack of or insufficient edema of the vulva and a low degree of ripening of the cervix. Another important indicator of approaching parturition, characteristic maternal behavior, was also severely affected (see Results).…”
Section: Discussionsupporting
confidence: 67%
“…Some of these signs, such as impaired labor (weak propulsive stage) and little preparation of the mammary gland, have already been described following transfer of both IVP bovine [25] and NT [3,44] ovine and bovine embryos. Our previous studies revealed a failure of maternal contribution to the labor of recipients carrying IVP and NT pregnancies [45][46][47], and here we observe further physiological deficiencies during the initial phase of parturition, including a lack of or insufficient edema of the vulva and a low degree of ripening of the cervix. Another important indicator of approaching parturition, characteristic maternal behavior, was also severely affected (see Results).…”
Section: Discussionsupporting
confidence: 67%
“…Wells et al [12] achieved a rate of 27.5% blastocysts when cultured adult mural granulosa cells were exposed to a cytoplast for a prolonged period of 4-6 h prior to activation; however, a direct comparison between IA and a 4-to 6-h incubation prior to activation (DA) was not performed in their study. The discrepancies in the results from various studies might also be explained by differences in selecting somatic donor cells (bovine embryonic stem-like cells vs. somatic cumulus cells) [31], age of oocyte recipients [32], experimental conditions [23], and protocols used [32][33][34]. Akagi et al [32] found that the DA method improved the in vitro development potential of NT embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo production from hormonally stimulated ewes (multiple ovulation and embryo transfer, MOET; ovum pick-up, OPU) is hindered by an unpredictable ovarian response [1]. A recent survey reveals that about 20% of sexually mature ewes do not respond to superovulatory treatments [2].…”
Section: Introductionmentioning
confidence: 99%
“…Even higher proportions of poor-or nonresponding donors were confirmed in prepubertal lambs [3][4][5] and calves [6]. 1 In ruminants, the variability in follicular response and capacity for embryos can be caused by several environmental factors like nutrition [7][8][9][10], management of animals [1,11], and season or photoperiod [2]. Another factor influencing developmental competence of oocytes is the timing of hormonal stimulation relative to the stage of estrus cycle [12].…”
Section: Introductionmentioning
confidence: 99%